2010
DOI: 10.1111/j.1365-2249.2010.04090.x
|View full text |Cite
|
Sign up to set email alerts
|

Rearing environment affects development of the immune system in neonates

Abstract: SummaryEarly-life exposure to appropriate microbial flora drives expansion and development of an efficient immune system. Aberrant development results in increased likelihood of allergic disease or increased susceptibility to infection. Thus, factors affecting microbial colonization may also affect the direction of immune responses in later life. There is a need for a manipulable animal model of environmental influences on the development of microbiota and the immune system during early life. We assessed the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 43 publications
4
43
0
1
Order By: Relevance
“…However, it is possible that piglets born into regularly sterilised farrowing accommodation may acquire a substantially different microbiota from the substrate than they would in an outdoor farrowing situation. This has indeed been shown in recent studies in pigs raised in different high v. low hygiene environments, which showed that such differences significantly affect not only intestinal microbiota composition but also the mucosal innate immune function in neonates, as well as in adult animals (Mulder et al, 2009;Inman et al, 2010).…”
Section: Gut Bacteria and Healthsupporting
confidence: 68%
“…However, it is possible that piglets born into regularly sterilised farrowing accommodation may acquire a substantially different microbiota from the substrate than they would in an outdoor farrowing situation. This has indeed been shown in recent studies in pigs raised in different high v. low hygiene environments, which showed that such differences significantly affect not only intestinal microbiota composition but also the mucosal innate immune function in neonates, as well as in adult animals (Mulder et al, 2009;Inman et al, 2010).…”
Section: Gut Bacteria and Healthsupporting
confidence: 68%
“…Additionally, decreases in IL2 and IFN-γ mRNA expression may represent a regional inhibition of the immune status that is associated with MHC-II expression (Zeitz et al 1988;Bravery et al 1995), which is consistent with the lower MHC-II expression detected in the present study (unpublished data). Although the rearing environment affects the development of the immune system in neonates (Inman et al 2010), the process takes time. Piglets in this study were newborn and euthanized shortly after birth without suckling.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, a possible probiotic effect of autochthonous B. choerinum was compared with that of probiotic E. coli Nissle 1917. Gnotobiotic pigs were used to avoid any effect of interindividual variation in intestinal microflora and rearing environment [27]. The distribution of bacteria, their translocation, the protective effect against subsequent infection with virulent Salmonella Typhimurium, the clinical state of experimental piglets and systemic and local production of two inflammatory cytokines – a chemokine, interleukin (IL)‐8, a proinflammatory cytokine, tumour necrosis factor (TNF)‐α and an anti‐inflammatory cytokine, IL‐10, were assessed.…”
Section: Introductionmentioning
confidence: 99%